Nanoparticle-based drug delivery systems with platinum drugs for overcoming cancer drug resistance. Issue 26 (12th June 2021) - Xie, Peng; Wang, Yushu; Wei, Dengshuai; Zhang, Lingpu; Zhang, Bin; Xiao, Haihua; Song, Haiqin; Mao, Xinzhan
Abstract : The mechanisms of chemoresistance and nanoparticle-based drug delivery systems for platinum drugs were detailed summarized in this review. The current combination therapy provided an effective strategy to overcome the platinum drug resistance. Abstract : Platinum drugs are commonly used in cancer therapy, but their therapeutic outcomes have been significantly compromised by the drug resistance of cancer cells. To this end, intensive efforts have been made to develop nanoparticle-based drug delivery systems for platinum drugs, due to their multifunctionality in delivering drugs, in modulating the tumor microenvironment, and in integrating additional genes, proteins, and small molecules to overcome chemoresistance in cancers. To facilitate the clinical application of these promising nanoparticle-based platinum drug delivery systems, this paper summarizes the common mechanisms for chemoresistance towards platinum drugs, the advantages of nanoparticles in drug delivery, and recent strategies of nanoparticle-based platinum drug delivery. Furthermore, we discuss how to design delivery platforms more effectively to overcome chemoresistance in cancers, thereby improving the efficacy of platinum-based chemotherapy.